Minimum Design Loads and Associated Criteria for Buildings and Other Structures. - (ASCE), American Society of Civil Engineers (Reston : American Society of Civil Engineers, 2021)
Standard ASCE/SEI 7-22 provides requirements for general structural design and includes means for determining various loads and their combinations, which are suitable for inclusion in building codes and other documents.
6.10.2.1 Overall Drag Force on Buildings and Other Structures.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books